Dispute Resolution Efforts for Sharia Banking Profit-Sharing Agreements - Mashudi, Yudi (Jurnal Indonesia Sosial Sains, 2024)
Islamic banking relies on profit-sharing agreements as one of its fundamental financial instruments, adhering to the principles of justice and partnership in sharia law. However, disputes often arise between banks and customers regarding the distribution of profits and losses. This study examines the dispute resolution mechanisms for profit-sharing agreements within Islamic banking, focusing on litigation in religious courts and non-litigation processes such as mediation and arbitration. This research aims to evaluate the effectiveness and compliance of these mechanisms with Sharia principles while also proposing improvements to regulatory frameworks. A mixed-method approach was employed, combining normative juridical analysis and empirical research. The normative juridical method was used to review existing laws and regulations related to Islamic banking and dispute resolution. At the same time, the empirical data was gathered through interviews with key stakeholders such as banking practitioners, customers, and mediators involved in dispute resolution. The results indicate that non-litigation mechanisms, particularly mediation, are more efficient and cost-effective than litigation. However, there remains a need for greater public understanding and stronger institutional support to ensure the fairness and transparency of these processes. This research recommends enhancing dispute resolution systems in Islamic banking, aligning them more closely with legal and sharia standards.